Three-dimensional computed tomography analysis of the mitral annulus for mitral annuloplasty in 100 cases of robotic mitral valve repair - Takahashi, Yosuke; Morisaki, Akimasa; Sakon, Yoshito; Nishiya, Kenta; Inno, Goki; Kawase, Takumi; Nishimoto, Yukihiro; Nagao, Munehide; Kishimoto, Noriaki; Noda, Kazuki; Shibata, Toshihiko (Frontiers in Cardiovascular Medicine, 2024)
Objectives: This study aimed to evaluate the efficacy of preoperative computed tomography in assessing the mitral annulus anatomy and posterior annular plication rate for mitral valve repair with annuloplasty.Methods: From July 2018 to August 2023, we performed robotic mitral valve repair with ring annuloplasty using a semi-rigid ring in 100 patients. Preoperative anatomical assessment of the mitral annulus by 3-dimensional computed tomography was done. The ring size was selected based on the perioperative commissure-to-commissure length or anterior leaflet area.The mean commissure-to-commissure, posterior mitral annular length, and minimum distance between the left circumflex artery and mitral annulus values were 31, 109, and 3.8 mm, respectively. No postoperative left circumflex artery injury or ring detachment were recorded. The mean plication rate (length of posterior side of the prosthetic ring /posterior annular length) was 0.68, which did not differ among each prosthetic ring size. Posterior plication rate (duplicate ring size 19.4) was a factor influencing the post-operative transmitral mean pressure gradient of 5 mmHg or higher.Freedom from moderate or severe mitral regurgitation was not different between the two groups above and below the posterior plication rate × ring size of 19.4 (p = 0.73), with an event-free rate of 97% versus 96% in three years, respectively.Conclusions: Preoperative evaluation of the mitral annular anatomy is useful for safe mitral valve repair with ring annuloplasty. Determining ring size by focusing on the posterior annular plication rate may be a new method for ring size selection.